2018
DOI: 10.1177/1120672118817687
|View full text |Cite
|
Sign up to set email alerts
|

Intense regulated pulse light for the meibomian gland dysfunction

Abstract: Purpose: To assess the effect of intense regulated pulse light (E-Eye; E-Swin, France) on the treatment of meibomian gland dysfunction. Setting: Health Sciences University, Ankara Numune Training and Research Hospital, Department of Ophthalmology. Methods: A total of 26 patients underwent intense pulsed light treatment (E-Eye; E-Swin), with homogeneously sequenced five light pulses delivered to one eye at 1, 15, and 45 days following baseline evaluation. At each visit, subjective clinical parameters (ocular su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 21 publications
(28 reference statements)
5
27
0
3
Order By: Relevance
“…The clinical safety and tolerability of IPL therapy have been confirmed by numerous clinical studies which report no major adverse events following IPL therapy [14,16,[19][20][21][22][23][24][25][26][27][28]. However, minor or transient side effects, including mild pain, light sensitivity, eyelash loss, eyelid erythema, crusting, hyperpigmentation, and blistering have been described [12,[29][30][31].…”
Section: Clinical Safetymentioning
confidence: 96%
See 1 more Smart Citation
“…The clinical safety and tolerability of IPL therapy have been confirmed by numerous clinical studies which report no major adverse events following IPL therapy [14,16,[19][20][21][22][23][24][25][26][27][28]. However, minor or transient side effects, including mild pain, light sensitivity, eyelash loss, eyelid erythema, crusting, hyperpigmentation, and blistering have been described [12,[29][30][31].…”
Section: Clinical Safetymentioning
confidence: 96%
“…The efficacy of IPL therapy has been reported by a large number of clinical studies. Retrospective and prospective nonrandomized studies have demonstrated that IPL therapy is associated with improvements in dry eye symptomology scores, tear film stability, tear osmolarity, lipid layer thickness, meibomian gland expressibility, meibum quality, eyelid margin vascularity and edema, conjunctival injection, corneal staining, and Schimer test values [12,16,[19][20][21][22][23][24][25][26][27]29,30,[34][35][36][37]. In addition, a recent prospective non-controlled study showed a reduction in tear inflammatory cytokines following IPL therapy [16], while another prospective controlled study reported significant improvement in tear protein and lipid content and composition [21].…”
Section: Clinical Efficacymentioning
confidence: 99%
“…MGE/IPL treatment also showed good clinical evolution after the application of objective and subjective DES tests [13]. However, Craig and Jiang, et al, when doing treatment without MGE, also reported signi icant improvement in the qualitative component of the lipid layer, TFRT, and symptomatic scores [17]. Therefore, further studies with more signi icant sample numbers are needed to evaluate isolated IPL and compared it with MGE-associated IPL [12].…”
Section: Treatment Eff Ectivenessmentioning
confidence: 99%
“…They found an improvement in tear ilm rupture time ( TFRT) and in the eyepiece lipid layer. This bene it was assessed from subjective symptom scores, SPEED form [17]. Toyos, et al analyzed 91 patients observed an improvement in TFRT and general symptoms in 87% -93% of cases [8].…”
Section: Treatment Eff Ectivenessmentioning
confidence: 99%
“…Meanwhile, Toyos reported a minimal reduction in tear osmolarity after IPL [8]. Nevertheless, this data is clinically irrelevant, as it does not interfere with symptoms [12,17]. Guilloto, et al demonstrated the relationship between IPL treatment refractoriness and previous eye surgery.…”
Section: Treatment Eff Ectivenessmentioning
confidence: 99%